Multisystem recovery after sport-related concussion in adolescent rugby players: a prospective study protocol - Chris Bleakley; Alan Rankin; Mark Matthews; Connor Shane McKee (BMJ Open)
Introduction Sport-related concussion is one of the most common injuries in adolescent rugby players with evidence of prolonged recovery in some concussed athletes. Concussion is a complex pathophysiological process that can affect a variety of subsystems with multifactorial presentation. Most research on adolescents recovery after concussion focuses on neurocognitive functioning and symptom outcomes over the short term. There is a need to explore concussion recovery over time across multiple subsystems in adolescent rugby players.Methods and analysis This prospective study will use sensorimotor and oculomotor outcomes in adolescent male and female rugby players aged 16–18 years. Players will be recruited from school or club rugby teams across the province of Ulster. Baseline assessment will be undertaken at the start of the playing season and will include questionnaires, Quantified Y Balance Test and Pupillary Light Reflex. Players who sustain a concussive event will be reassessed on all outcomes at 3 days, 7 days, 14 days, 23 days, 90 days, 180 days and 365 days postconcussion. For serial outcome data, we will examine response curves for each participant and make comparisons between known groups. We will use logistic regression to explore any association between demographic variables and recovery. The strength of the predictive model will be determined using R2, p values and ORs, with 95% CIs.Ethics and dissemination Ethical approval has been granted for this study from Ulster University Research Ethics Committee (REC/14/0060). This study will be published in an open-access research journal on completion.Trial registration number ACTRN12622000931774p.